SUSCEPTIBILITY OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE AMONG BIKE RIDERS IN BANGALORE USING BODE INDEX (International Journal of Physiotherapy, 2015)
Background: Air pollution as a trigger for exacerbation of COPD has been recognized for more than 50 years. Nowadays, in the cities like Bangalore, most of the people need to ride the bike for their occupational demand and move around. The purpose of this study is to find out the prediction of COPD using the BODE index in motor bike riders in Bangalore.Methods: An exploratory cross sectional study has been done on 100 subjects who uses motor bike as their mode of transport for their occupational demand, to study the hours of bike riding with the chances of COPD based on BODE index.Results: Analysis using spearman rank correlation found that there is statistically significant correlation (p < 0.05) between hours of bike riding and the BODE index. Chi square test found that more than 4 hours of bike riding was associated with the chances of COPD.Conclusion: Based on the result, it is concluded that more than 4 hours of bike riding is associated with the chances of developing COPD even in non-smokers. Therefore there is significant susceptibility of COPD among bike riders in Bangalore.